2015
DOI: 10.1007/s12262-015-1393-6
|View full text |Cite
|
Sign up to set email alerts
|

Management of Liver Trauma in Minia University Hospital, Egypt

Abstract: The aim of this study is to present the outcome of operative and non-operative management of patients with liver injury treated in a single institution depending on imaging. This study was conducted at the Causality Unit of Minia University Hospital, and included 60 patients with hepatic trauma from March 2012 to January 2013. In our study, males represent 80 % while females represent 20 % of the traumatized patients. The peak age for trauma found was 11-30 years. Blunt trauma is the most common cause of liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…NOM could be the choice depends on the severity of liver blunt trauma and associated injuries. 5,7 Kozar et al, in his study revealed that global complication rate of NOM is 14 % but for grade V injuries the rate was higher around 52%. 31 Grade of liver injury can reflect the degree of hepatic parenchymal damage.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…NOM could be the choice depends on the severity of liver blunt trauma and associated injuries. 5,7 Kozar et al, in his study revealed that global complication rate of NOM is 14 % but for grade V injuries the rate was higher around 52%. 31 Grade of liver injury can reflect the degree of hepatic parenchymal damage.…”
Section: Discussionmentioning
confidence: 98%
“…1,3,5,16 Management of liver injury depends on patient's condition, diagnosis, transfusion requirement, complication, as well as the hospital facilities to make a diagnosis and treatment. Non-operative management of liver injuries has gained wide support and adopted for approximately 80% of blunt liver injuries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations